CT Score as a Mainstay of Tocilizumab Treatment in COVID-19 - Terkes, Vedrana; Tolic, Anela; Morovic, Miro (International Journal of Innovative Research in Medical Science, 2021)
Background: After one year of numerous clinical trials, the position of tocilizumab in the treatment of COVOD-19 patients is not yet stable. Methods: In this small prospective observational study, we recruited patients with severe and critical COVID-19 with a rapid deterioration of their clinical status. Demographic, clinical, CT findings and laboratory data were collected prior to the decision to administer tocilizmab. Results: 33 patients were included between March 2020 and February 2021 11 (33.3%) of patients died, with the median of 22.5 (9-35) days (p<0.05). Compared with the survivors, the patients who died were significantly older, with the mean age of 72.5 years vs 61.3 years, respectively. Also, the mean CT scores in the patients who died were significantly higher than in the survivors, with the mean value of 22.7 vs 17.3 (p<0.05). In addition, there was also a difference in the mean values of inflammatory parameters, which were generally higher in non-survivors. Conclusion: In this small exploratory analysis of 33 patients with severe or critical COVID-19, treated with tocilizumab we did not obtain neither a significant reduction of ICU admission neither of mortality. The high CT grade of lung damage has shown to be the only independent prognostic factor of clinical outcome, regardless of administration time or criteria of tocilizumab use.